A (re)organização operacional da administração pública proposta pela consensualidade - Correa, Sergionei (Universidade do Vale do Rio dos Sinos, 2017)
From the proposed theme; the route of (re) operational organization of Public Administration for the treatment of administrative conflict proposed by consensuality, the following problem has emerged: the period of (re) readings in the structuring elements of State, law and Public Administration is a fertile ground for the insertion and maturation of consensuality as a mechanism for the treatment of administrative conflicts? Also, how to internalize the consensual logic in the Administration to reduce administrative conflicts and contribute in its process of operational (re) orientation? In order to answer, the hermeneutic methodology to remove the innumerable layers of language incident on the theory of State, law and operational logic in the Administration, enabling the disclosure of consensuality as the matrix of operational (re) orientation of the Public Administration for the treatment of administrative conflicts. Therefore, the objective of the research was to investigate the process of (re) organization in the Administration for the treatment of administrative conflicts proposed by consensuality in view of the contemporary scenario of (re) readings in: State, society and law. The following hypotheses were elaborated to analyze the process of (re) re-reading in the State, Law and Administration; (re) thinking about traditional treatment mechanisms and the very design of the conflict; to investigate the importance of kairological time for consensual mechanisms; study the institutional performance of state law firms, particularly the AGU in the process of (re) organization of operational logic of Public Administration for the treatment of administrative conflicts. It can be concluded that the period of (re) readings in transit is fertile for the insertion and maturation of consensuality for the treatment of administrative conflicts, presenting, from a process of internalization and organization in State Advocacy, an alternative feasible to consolidate the course of (re) reading the operational logic of the Brazilian Public Administration in the face of administrative conflicts.
Keywords: Consensualidade; Administração pública; Conflitos administrativos; Tempo kairológico; Advocacia de estado; Consensuality; Public administration; Administrative conflicts; Kairological time; State advocacy; ACCNPQ::Ciências Sociais Aplicadas::Direito